(untitled) (Medicine Today, 2021)
Introduction: The study carried out among the pregnant women who had anemia during pregnancy with the objectives to determine their maternal outcome at private hospitals in Dhaka city. Materials and Methods: The total sample size was 110. Data was collected by interviewing the respondents with a structured pre-tested questionnaire. The study was conducted in pregnant women with anemia at or after 28 weeks of gestation and had delivered at Obstetrics Department of Ad-Din Barrister Rafique ul-Huq Hospital, Jurain and Bashundhara Ad-Din Medical College Hospital South Keranigonj. Results: Most of the respondents (38.2%) belonged to the age group between 16-20 years. The mean age was 23.74±5.127 years. Almost (49.1%) up to primary & (38.2%) were up to secondary/higher secondary level. Most of the respondents were homemaker (87.3%); Monthly income means was 19340.91±12459.647. Most (90.9%) of the respondents had received ANC and 79.1% respondent’s hemoglobin level was below 10 gm. /dl. Among them 90.9% of the respondent’s fetal outcome were healthy & alive baby. More than half (51.8%) of the respondent’s baby were _ 2.5 kg birth weight. Study also shows that 55.5% respondents had anemia after delivery, 28.2% had sickness and 22.7% were sulfured with complications after delivery. There was a significant relationship with low birth weights (LBW) to less high education. Conclusion: All women should be given advice regarding diet in pregnancy with details of foods rich in iron. Dietary changes alone are not sufficient to correct an existing iron deficiency in pregnancy and iron supplements are necessary. Medicine Today 2021 Vol.33(2): 102-107